2007
DOI: 10.1021/jp067862s
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale View of Redox-Induced Reversible Changes to a Metal-Oxide Catalytic Surface:  VOx/α-Fe2O3(0001)

Abstract: X-ray standing wave (XSW) analysis and X-ray photoelectron spectroscopy are used to trace the electronic and atomic-scale structural changes of a supported vanadium oxide system at different stages of its oxidationreduction cycle. Both the oxidation state and adsorption geometry of the vanadium oxide and its R-Fe 2 O 3 -(0001) single crystal support show reversible changes through the oxidation-reduction cycle characteristic of catalytic behavior. The 3D V atomic distribution maps, derived from the summation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 25 publications
2
32
1
Order By: Relevance
“…7, where we can see that the 1 ML oxidized V distribution is similar to the 0.5 ML reported case [2], except that the B/A relative site occupation fraction ratio is higher for 1 ML. Interpreting these results further: the A-site (closer to underlying oxygen layer) appears stable with respect to the coverage change, existing in both 0.5 ML and 1 ML as-deposited surfaces.…”
Section: Comparison Of Experiments With Theorysupporting
confidence: 76%
See 1 more Smart Citation
“…7, where we can see that the 1 ML oxidized V distribution is similar to the 0.5 ML reported case [2], except that the B/A relative site occupation fraction ratio is higher for 1 ML. Interpreting these results further: the A-site (closer to underlying oxygen layer) appears stable with respect to the coverage change, existing in both 0.5 ML and 1 ML as-deposited surfaces.…”
Section: Comparison Of Experiments With Theorysupporting
confidence: 76%
“…Experimental studies of submonolayer V adsorption on clean hematite (0 0 0 1) with subsequent repeatable oxidization/reduction cycles were reported by Kim et al [2], using atom-resolved X-ray standing wave measurements (XSW) to detect V site geometry and X-ray photoemission spectroscopy (XPS) to detect electronic structure changes. In I the general experimental and theoretical background was presented, and theoretical methodology was described.…”
Section: Introductionmentioning
confidence: 99%
“…PDOS of the surface atoms in these three monomer configurations are shown in Figure S3 (0001) substrate with the specified terminal ligands: [70]. Rudimentary assumptions about substrate-induced strain suggest that the dimers and chains might be more likely to "stretch apart" on the hematite surface as the lateral lattice parameter of the hematite cell (a = 5.01 Å) is 5.3% larger than that of sapphire (a = 4.76 Å).…”
Section: Resultsmentioning
confidence: 99%
“…Exposure of the V films to atomic oxygen resulted in the formation of V 2 O 5 , and the reoxidation of the surface Fe [342]. In subsequent XSW studies [551], the authors demonstrated a clear link between the oxidation state of the V, and its position with respect to the iron-oxide substrate. Hydration (through exposure to air) also oxidises the V to V 5+ , although it can be reduced again by annealing at 773 K in H 2 [553].…”
Section: +mentioning
confidence: 93%